Hydraulic differences along the water transport system of South American Nothofagus species: do leaves protect the stem functionality? - Bucci, S. J.; Scholz, F. G.; Campanello, P. I.; Montti, L.; Jimenez-Castillo, M.; Rockwell, F. A.; Manna, L. L.; Guerra, P.; Bernal, P. L.; Troncoso, O.; Enricci, J.; Holbrook, M. N.; et al. (Tree physiology, 2012)
Hydraulic traits were studied for six Nothofagus species from South America (Argentina and Chile), and for three of these species two populations were studied. The main goal was to determine if properties of the water conductive pathway in stems and leaves are functionally coordinated and to assess if leaves are more vulnerable to cavitation than stems, consistent with the theory of hydraulic segmentation along the vascular system of trees in ecosystems subject to seasonal drought. Vulnerability to cavitation, hydraulic conductivity of stems and leaves, leaf water potential, wood density and leaf water relations were examined. Large variations in vulnerability to cavitation of stems and leaves were observed across populations and species, but leaves were consistently more vulnerable than stems. Water potential at 50% loss of maximum hydraulic efficiency (P(50)) ranged from -0.94 to -2.44 MPa in leaves and from -2.6 to -5.3 MPa in stems across species and populations. Populations in the driest sites had sapwood and leaves more vulnerable to cavitation than those grown in the wettest sites. Stronger diurnal down-regulation in leaf hydraulic conductance compared with stem hydraulic conductivity apparently has the function to slow down potential water loss in stems and protect stem hydraulics from cavitation. Species-specific differences in wood density and leaf hydraulic conductance (K(Leaf)) were observed. Both traits were functionally related: species with higher wood density had lower K(Leaf). Other stem and leaf hydraulic traits were functionally coordinated, resulting in Nothofagus species with an efficient delivery of water to the leaves. The integrity of the more expensive woody portion of the water transport pathway can thus be maintained at the expense of the replaceable portion (leaves) of the stem-leaf continuum under prolonged drought. Compensatory adjustments between hydraulic traits may help to decrease the rate of embolism formation in the trees more vulnerable to cavitation.